It Takes Time to Be Cool: On the Relationship between Hyperthermia and Body Cooling in a Migrating Seaduck - Guillemette, Magella; Polymeropoulos, Elias T.; Portugal, Steven J.; Pelletier, David (Frontiers in Physiology, 2017)
The large amount of energy expended during flapping flight is associated with heat generated through the increased work of the flight muscles. This increased muscle work rate can manifest itself in core body temperature (Tb) increase of 1-2 oC in birds during flight. Therefore, episodic body cooling may be mandatory in migratory birds. To elucidate the thermoregulatory strategy of a short-distance migrant, common eiders (Somateria mollissima), we implanted data loggers in the body cavity of wild birds for one year, and report information on Tb during their entire migration for 19 individuals. We show that the mean body temperature during flight (TbMean) in the eiders was associated with rises in Tb ranging from 0.2 to 1.5 o C, largely depending on flight duration. To understand how eiders are dealing with hyperthermia during migration, we first compare, at a daily scale, how Tb differs during migration using a before-after approach. Only a slight difference was found (0.05 oC) between the after (40.30 oC), the before (40.41 oC) and the migration (40.36 oC) periods, indicating that hyperthermia during flight had minimal impact at this time scale. Analyses at the scale of a flight cycle (flight plus stops on the water), however, clearly shows that eiders were closely regulating Tb during migration, as the relationship between the storage of heat during flight was highly correlated (slope = 1) with the level of heat dumping during stops, at both inter-individual and intra-individual levels. Because Tb at the start of a flight (TbStart) was significantly and positively related to Tb at the end of a flight (TbEnd), and the maximal attained Tb during a flight (TbMax), we conclude that in absence of sufficient body cooling during stopovers, eiders are likely to become increasingly hyperthermic during migration. Finally, we quantified the time spent cooling down during migration to be 36 % of their daily (24 h) time budget, and conclude that behavioural body cooling in relation to hyperthermia represents an important time cost.